China: The Impacts of COVID-19 on Migrants, Household Income, and Poverty - Diao, Xinshen (2020)
Xinshen Diao POLICY SEMINAR Virtual Event - Evolving effects of COVID-19 on poverty and food security: What are we learning from China? JUL 28, 2020 - 09:30 AM TO 10:45 AM EDT